2002
DOI: 10.1007/s004200100289
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of Karasek's demand and control scales within a single sector: data from a large teaching hospital

Abstract: Apart from some guarded uncertainty over what the demands scale may be measuring, overall, the two scales appeared to perform reasonably well in this sample of health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 14 publications
(25 reference statements)
8
42
2
2
Order By: Relevance
“…However, the mean scores of decision latitude were much lower, especially the decision authority subscale; whereas the mean scores of psychological job demands scale were slightly higher compared to western countries. As regards standard deviations, they were consistent with other studies 8,31,32) . Due to the restricted occupational category (health care workers), the differences were likely to be of consideration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the mean scores of decision latitude were much lower, especially the decision authority subscale; whereas the mean scores of psychological job demands scale were slightly higher compared to western countries. As regards standard deviations, they were consistent with other studies 8,31,32) . Due to the restricted occupational category (health care workers), the differences were likely to be of consideration.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the gender differences could be observed in our study. The skill discretion and decision authority in women were systematically lower across not only this study, also all other countries' studies 8, 27,[31][32][33][34][35]37) . This finding indicated that women had less freedom for their own job in the psychosocial work environment, they would be more susceptible to the poor condition therefore.…”
Section: Discussionmentioning
confidence: 47%
“…In another study which included five questions of the psychological demand scale [32], the EFA also extracted these three items uniformly on the psychological demand factor while the other two items of 'work fast' and 'work hard' loaded on physical demand. Our CFA finding that psychological demand was appropriately separated into two distinct subscales was in agreement with Sale's study among health care workers [23] which provided a better goodness of fit for the two-factor model when compared against the original one-factor psychological demand model. The two factors connected with the psychological demand scale in our study were associated with time constraints and conflicting demand at work and may be redundant with each other.…”
Section: Confirmatory Factor Analysissupporting
confidence: 89%
“…The internal consistency of psychological demand in our study was the lowest compared to other studies with Cronbach's alpha of 0.23 for five questions of 22-item TJCQ and 0.54 for nine questions of 45-item TJCQ. Some western studies have reported acceptable Cronbach's alpha values of more than 0.7 for the psychological demand scale [20][21][22][23][24] while some have reported borderline alpha values around 0.6 [17,25]. The psychological demand scale, with five questions, was borderline in all Asian studies with alpha values ranging from 0.50-0.65 [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy over these two ways of measuring psychosocial risk factors is mainly directed at the validity of the worker's perception as a measure of psychosocial factors at work [3][4][5] . A number of studies have assessed psychosocial risk factor instruments by using three different approaches: (a) comparing the scores given by the instrument according to some selected key variables, such as sex, age or occupation 6) ; (b) evaluating the associations of psychosocial factors with health outcomes 7) ; and (c) examining correlations among psychosocial factors themselves 8) . Nevertheless, none of these approaches has assessed the validity of measurement, understanding validity as an expression of the degree to which a measurement measures what it purports to measure 9) .…”
mentioning
confidence: 99%